PROBLEMA GURU NON SERTIFIKASI SMA SWASTA DI KOTA PADANG - Nurul Aficha; afdhal afdhal (JURUSAN GEOGRAFI FIS UNP, 2020)
ABSTRACT This article is intended to determine the condition of non-certified private high school teachers in the city of Padang as well as to find out what factors are causing private high school teachers in the city of Padang to find certification both externally and internally. Using qualitative research with the type of case study research. The selection of informants is done by purposive sampling. Phase-data sources used are primary data and secondary data. Data collection techniques used were observation, interviews, documentation. Data analysis techniques used include; Collecting data, data reduction, data presentation, and conclusion conclusions. The results of this study indicate how teachers in Padang private high schools and the factors that cause private high school teachers in Padang are few who get certified. The conditions obtained are 1) low welfare level, 2) low health level, 3) incompetent practice. While the factors found there are external and internal factors. External factors are as follows 1) the difficulty of the PPG procedure, 2) lack of teaching hours obtained, 3) do not have a permanent foundation. The internal factors are as follows 1) not optimal in making learning plans, 2) the absence of professional development work, 3) non-participation in scientific forums, 4) no experience educational and social organizations, 5) did not get awards that were relevant to the field of education.